HUMOR KEKERASAN FILM ANAK-ANAK TELEVISI INDONESIA DALAM PERSPEKTIF FILSAFAT ANALITIS LUDWIG WITTGENSTEIN - , ENDAH AGUSTIANI; , Dr. M. Mukhtasar Syamsuddin ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The reseach on humor violence in film of children in Indonesia television which is related to establishment mindset and to understand the reality of the viewers represent an efforts to understand the correlation between television and the viewers, in case how if the viewers watch intensively the television that can affect their mindset and children ability in understanding reality. In order to accomplish the research, the reseacher employs This reseach is a study case through literature research, which uses philosophical hermeneutic as a method to analyze data. In this method the reseacher use some methodical elements as follows: 1) Analysis, to do an explanation and interpretation of data, 2) Internal coherence, to see the correlation between material and formal object inside a consistent structure, 3) Interpretation, is an effort to intercept the meaning, value, and purpose from reality (facts, data, and phenomenon), 4) Inclusive language or analogal, adapt with the system in the reseach object, and 5) Description, to give a comprehensive view of the meaning that occurs in object research. The result in this research are: 1)theory of analytical philosophy of Ludwig Wittgenstein as a formal object, since the theory emphasizes the logical and ordinary languages games which are used to build logical picture of the facts. In other words, the worldâs reality can be understood within the logical language and is widely acceptable through ordinary language. Sensuality and violence becomes an important element in humor, especially in the children film and it is not apart from them. Nowadays, the impression of humor violence, and humor as the main package to present the violence so everyone can enjoy it, as if it a legal thing, 2) theory of analytical philosophy Wittgenstein not apart from an effort and main concern to understand the reality, but in different ways. Its to figure out the reality of the world with logical language and the essence of language is from exercise in human daily activity which has pluriformity (language games), and 3) The understanding of reality through language games is correlated with natural processes of the application of language since children, in its development is an empiric phenomenon. But unfortunately, what is perceived in children films, it canât represent the entire reality, because it has obscured the causal impact significantly.